Knowledge of Occupational Skills of Youth Based on Community Identity with Royal Science, Island Area, Satun Province - Vehachart, Rungchatchadaporn; Wetwiriyasakun, Phatsarabet; Srisakda, Venus; Yangchin, Somkiat; Tipdech, Orapin; Sirirattanajitt, Aphinant (Arts of Management Journal, 2024)
This research aims to 1) study the knowledge and occupational skills of youth based on community identity with royal science, the island area, and Satun Province, and 2) study the process of developing the occupational skills of the youth. This qualitative research determines the main group of qualitative informants by purposive selection in 11 communities in the island area, Satun Province. It is a field study conducted to study the wisdom and knowledge in the community that can lead to the development of occupational skills that are the identity of the community, according to King’s science. An in-depth interview was carried out with representatives of villagers in 11 communities, with 2 representatives from each community (totaling 22 participants), along with a focus group discussion with community leaders to organize the knowledge system of vocational skills and study the needs of the process of developing the vocational skills of youth. Qualitative data analysis was performed using content analysis. The research findings revealed that 1) the study of knowledge and occupational skills of youth based on community identity with royal science in the Satun Province island area in connection with community context, community identity, local wisdom, and living problems led to the identification of three main occupational groups: 1) product production utilizing local resources; 2) fishermen; and 3) tourism. These occupational groups reflect the local identity and culture of the island community and are integral to their way of life; and 2) the results of the study of the process of developing the vocational skills of youth based on community identity with royal science in the island area Satun Province. Knowledge management using the community as a base consists of four steps: 1) determine knowledge connection issues; 2) gather in groups to extract lessons and exchange knowledge; 3) summarize knowledge; and 4) transfer knowledge back to the community.